Teacher Competences for Facing Challenges of Globalisation in Education - Auziņa, Anita (Journal of Education Culture and Society, 2018)
Aim. The aim of the research is to explore the characteristics of globalisation and highlight challenges resulting from the globalisation process in the teaching profession. Teachers are to be prepared to face any influence the globalisation brings in education: heterogeneous, diverse and multicultural classrooms due to the rise of migration, immigration and remigration; society’s expectations of and demands on the teacher regarding the learning process, its content and competences that students should develop to be prepared for their future. Methods. The author carried out surveys among 205 pre-service and 110 in-service teachers; the paper focuses on the presentation of respondents’ opinions regarding competences teachers need to be able to face the challenges of globalisation entering the sphere of education in general and their own classrooms. Results. The analysis showed competences that today’s teachers should have and demonstrate to be competent professionals and also role models for their students in the context of contemporary globalisation. Conclusion. The study showed the characteristics of globalisation that have an impact on education. The emphasis was given to the existing society’s expectations of and demands on the teachers, highlighted in the literature and the surveyed respondents’ answers. As a result of the study, the following relation was found: to be able to identify the knowledge and skills teachers need to handle complexity and face the challenges of globalisation entering the sphere of education, one has to understand the nature and characteristics of globalisation.